EVALUASI SISTEM REMUNERASI DOSEN BADAN LAYANAN UMUM PERGURUAN TINGGI (Studi Kasus Universitas “X”) - Vidia Alif Agrimahera; Helmy Adam (Jurnal Ilmiah Mahasiswa FEB, 2013)
This research aims to evaluate lecturer remuneration system in University’s Public Service Agency. The Evaluation process is conducted based on the observance of laws and regulations. This research uses qualitative descriptive method. Researcher as the key  instrument. The data obtained through interviews and document collection. The result of the research show that the remuneration system “X” University meets the principle of fair, equitable and  reasonable. The principle of  proportionality, equality and appropriateness in accordance  to PP Nomor 23 Tahun 2005 and PMK Nomor 10 Tahun 2006. legislation and regulations. But a lack of transparency and a single salary. Nevertheless  the principle of  transparency and  the single  salary has not been carried out in accordance  with  laws and regulations.  Researchers  propose  model of remuneration in accordance with the regulations. Keywords: remuneration, Public Service Agency, university, lecturer